2014
DOI: 10.1038/gene.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the pathogenic molecular sub-phenotype interferon-alpha identifies multiple novel loci involved in systemic lupus erythematosus

Abstract: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disorder characterized by inflammation of multiple organ systems and dysregulated interferon responses. SLE is both genetically and phenotypically heterogeneous, greatly reducing the power of case-control studies in SLE. Elevated circulating interferon alpha (IFN-α) is a stable, heritable trait in SLE, which has been implicated in primary disease pathogenesis. 40–50% of patients have high IFN-α, and high levels correspond with clinical differences. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 52 publications
(67 reference statements)
3
46
0
1
Order By: Relevance
“…To control for genetic ancestry and admixture, we genotyped 332 ancestry-informative markers (AIMs) designating continental ancestry in all of our cases and controls, as described in [38]. The AIMs data were analyzed using principal component analysis, and the first principal component designated African vs. non-African ancestry, as would be expected.…”
Section: Methodsmentioning
confidence: 99%
“…To control for genetic ancestry and admixture, we genotyped 332 ancestry-informative markers (AIMs) designating continental ancestry in all of our cases and controls, as described in [38]. The AIMs data were analyzed using principal component analysis, and the first principal component designated African vs. non-African ancestry, as would be expected.…”
Section: Methodsmentioning
confidence: 99%
“…ITGAM SNPs correlate with elevated IFN-I activity in SLE patients. (A) Functional IFN-I activity, as determined using reporter cell assay (3,78), in serum samples from 171 SLE subjects genotyped for 3 ITGAM SNPs (rs1143678, rs1143679, and rs1143683) and its association with minor allele carriers compared with carriers of major alleles, stratified by high versus low IFN-I levels. Each dot represents a unique sample.…”
Section: Sle Subjects Carrying Itgam Snps Have Significantly Elevatedmentioning
confidence: 99%
“…Studies have been conducted to identify novel genetic risk factors for SLE using serum IFN as the genetic trait and determining which genetic polymorphisms are associated with high IFN levels in lupus patients 3941 . These studies have demonstrated number of novel polymorphisms, including PNP and PRKG1 41 , which have not been reported in case-control design studies, suggesting that the study of sub-phenotypes within SLE will be important to fully map the genetic architecture of the disease. The model would be that the genetic variations induce functional genetic changes, which then modulate important immune system phenotypes such as type I IFN or autoantibodies, and then these immune system phenotypes impact disease manifestations (See Figure 1).…”
Section: Type I Interferon: Pathogenic Immune System Phenotype Regulamentioning
confidence: 99%